GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 364 species occurrences available in GBIF matching the query: TaxonKey: Vipera ammodytes Bruno, 1968. The dataset includes 364 records from 45 constituent datasets: 1 records from MVZ Herp Collection (Arctos). 1 records from Herpetile collection, Natural History Museum, University of Oslo. 1 records from Reptilia Collection of Museum and Institute of Zoology PAS. 1 records from Zoology (Museum of Evolution - Uppsala). 30 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 41 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Herpetology. 2 records from MPM Herpetology. 5 records from Museum of Comparative Zoology, Harvard University. 13 records from iNaturalist Research-grade Observations. 9 records from NRM-Herpetology. 8 records from naturgucker. 11 records from AMNH Herpetology Collections. 12 records from CM Herps Collection. 34 records from Natural History Museum (London) Collection Specimens. 1 records from LSUMZ Herp Tissues. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 13 records from NMNH Extant Specimen and Observation Records. 1 records from Collection Herpetologie - SNSD. 6 records from LSUMZ Herps Collection. 5 records from MSUM Ichthyology and Herpetology Collections. 3 records from Paleobiology Database. 4 records from SDNHM Herpetology Collection. 1 records from TNHC Herpetology Collection. 3 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 4 records from Herpetology. 15 records from UTA Herpetology. 7 records from UMMZ Herpetology Collection. 1 records from Natural History Museum, University of Tartu. 2 records from Collection Herpetology SMF. 8 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 10 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 2 records from Ditsong National Museum of Natural History Collection: 1805-2008. 15 records from SMNS Herpetologie. 12 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 12 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 28 records from UTEP Vertebrates. 4 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 4 records from CAS Herpetology (HERP). 5 records from Paläoherpetologie - SMF. 1 records from KUBI Herpetology Collection. 10 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 12 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences